High Concentration Lithium Nitrate/Dimethylacetamide Electrolytes for Lithium/Oxygen Cells. Issue 13 (30th September 2016) - Giordani, Vincent; Uddin, Jasim; Bryantsev, Vyacheslav S.; Chase, Gregory V.; Addison, Dan
Abstract : A high concentration of lithium nitrate (LiNO3 ) in dimethylacetamide (DMA) is shown to exert an inhibitory effect on electrolyte degradation processes in a rechargeable Li/O2 battery. Experimental observations are supported by quantum chemical calculations suggesting that resistance of the solvent to autoxidation and hydrogen atom abstraction may improve in proportion to Li salt concentration. Both in situ and ex situ gas analysis data reveal a trend of a reduced rate of electrolyte decomposition at higher concentrations of LiNO3 . Additionally, characterization of the surface and interface of both the O2 and Li electrodes, including X-ray photoelectron spectroscopy (XPS), electrochemical impedance spectroscopy (EIS) and X-ray diffraction provide further evidence for improved electrolyte stability at higher Li salt concentration and the mechanistic theory thereof.